2023
DOI: 10.1002/admt.202201778
|View full text |Cite|
|
Sign up to set email alerts
|

Building Blood Vessel Chips with Enhanced Physiological Relevance

Abstract: Due to the bioengineering nature, tissue chips allow the manipulation of cellular composition [11] and a range of biophysical and biochemical environmental cues, including but not limited to cell-ECM interactions, dynamic flows, chemical species gradients, substrate stiffness, [12] and active mechanical stimuli. [13,14] In particular, the on-chip adoption of patients' cells, either primary or induced human pluripotent stem cells (hiPSCs), makes a bespoke and patient-specific tissue model in line with the goal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 359 publications
0
2
0
Order By: Relevance
“…In our patient, it's evident that the considerable length of the vascular prosthesis utilized resulted in an angulation that disrupted the linear geometry. This deviation in the prosthesis geometry is the primary factor behind the escalated shearing forces and heightened localized rigidity, ultimately culminating in the gradual erosion of the surrounding tissues and subsequent exposure of the prosthesis [7,8]. A lot of treatment options for graft infection/exposure exist.…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, it's evident that the considerable length of the vascular prosthesis utilized resulted in an angulation that disrupted the linear geometry. This deviation in the prosthesis geometry is the primary factor behind the escalated shearing forces and heightened localized rigidity, ultimately culminating in the gradual erosion of the surrounding tissues and subsequent exposure of the prosthesis [7,8]. A lot of treatment options for graft infection/exposure exist.…”
Section: Discussionmentioning
confidence: 99%
“…[164] More interestingly, some studies show that microgels can flow safely through capillary-mimicking microchannels, as long as they fit within certain physical requirements of size and deformability. [122] With the growing investment in in vitro and in silico technologies such as blood vessel-onchip [165][166][167][168] and microcirculation simulations, [169][170][171] microparticle safety profiles are expected to be traced at a faster pace. These advances will hopefully draw a clearer picture on microparticle safety in intravascular injection.…”
Section: Size Rangementioning
confidence: 99%
“…Since then, four silk-based biomedical materials have been commercialized, including bioresorbable surgical mesh (SERI Surgical Scaffold ® ) [ 22 ], silk fabric (MICROAIR DermaSilk ® ) for atopic dermatitis in children [ 23 , 24 ], a silk patch (Tympasil) for acute tympanic membrane perforation treatment [ 25 ], and a silk fibroin wound dressing (Sidaiyi) [ 26 ]. With its superior biocompatibility, controllable biodegradation into noninflammatory byproducts, aqueous processibility, compatibility with sterilization, robust mechanical and thermal properties, and sufficient supply, silk has become a popular biomaterial for drug delivery, as a biosensor, and for tissue engineering [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. It has been shown that silk is able to encapsulate a variety of molecules, including protein HIV inhibitors, antibodies, and small molecules, with multiple modalities such as 3D porous scaffolds, films, gels, particulates, and microneedle patches, contributing a desired drug delivery system as a microbicide [ 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%